The importance of state budget expenditure management for the cause of education in phu tan district – Ca Mau province - Nguyễn, Văn Oanh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Effective budget management and utilization is one of the most essential prerequisites for any unit or organization to fulfill its responsibilities in the context of economic and social development. How to manage state budget expenditures at educational institutions in Phu Tan district, Ca Mau province, to ensure the highest efficiency, thoroughly save, and overcome overspending, improper competence, and incorrect provisions of the State Budget Law is of utmost concern to the Party and local authorities in order to meet the requirements of development in the innovative period and international economic integration of the local area. Based on descriptive statistics, synthesis, analysis, and comparison, this study has highlighted the importance of state budget expenditure management for the cause of education in Phu Tan district, Ca Mau province, for the period 2019–2021, by proposing directions and solutions to enhance the state budget expenditure management process for education and training to achieve the desired results.